Community ecology, taxonomy and geographic distribution of the deep-sea shrimps in northeastern Brazil - ALVES JÚNIOR, Flavio de Almeida (2019)
The Potiguar Basin was formed in mesocenozoic age occurring between the States of Ceará and Rio Grande do Norte, being target of several cientific researches, especially by environmental agencies promoved by private initiative and public agents, due its great biological wealth and mineralogical in this region. However in Potiguar Basin, the environmental studies are being focused especially in costal zones, thus making deep-sea aspects nonexistent along the continental slope (> 200 m) still unknown, principally in aspects about the deep invertebrate biodiversity.Similar aspects about the little knowledge of the deep invertebrate biodiversity are observed for the regions of oceanic Islands, as for exemple, in Fernando de Noronha Archipelago, Atoll as Rocas Atoll and seamounts as those registered in North Ceará Chain. Due to this, this theses has as objective analyse the community structure of the deep-sea shrimps occurring in Potigar basin and report the taxonomic composition and distributional aspects of deep-sea shrimps in Potiguar Basin, oceanic Islands and seamounts in the Brazilian Northwestern region.The samples were collected in two different areas. First in the Potiguar Basin, located in the northeast of Brazil between (03/05° S; 38/35° W), in the states of Ceará (CE) and Rio Grande do Norte (RN), under the framework ofthe project “Avaliação da biota bentônica e plânctonica da Bacia Potiguar e Ceará (Bpot)”, on board theR/V Luke Thomas in 2009 and by R/V Seward Johnson in May 2011, with bottom trawls conducted on the continental slope using a semi-balloon otter trawl with 50 mm of mesh size and 18 m of mouth opening, between the isobaths of 150, 400, 1000 and 2000 m. After, samples collected during the framework of project ABRAÇOS (Acoustic along the Brazilian coast), on Fernando de Noronha Archipelago, Rocas Atoll and Seamounts in Ceará Chain, which occurred in October 2015 and April of 2017, through the water column by using the drag of a micronekton net with 1 mm of mesh, with stations (#ST) between 10–1660 m depth. From Potiguar Basin, were collected 49 species, being represented by 15 families, while in oceanic islands were sampled 27 species belonging to 5 families. For the Potiguar Basin, the distribution of the shrimps showed associated with the water mass, being the abiotic factos dodominant in vertical distribution. The high indices of richness ware observed in depth of 400 and 1000 m, and the low values being associated with deeper water mass. The highest peaks of diversity were observed at depth of 1000 m, with the deeper stations showing the lower values. Along the analysis of community, were observed species descriptors of water mass, which are restrict only abiotic factors action in each depth. The informations showed herein; highlight the first observations about the aspects thar governing the deep-sea shrimps community occurring in Potiguar basin, beyond of the taxonomic composition and distributional aspects of this deep fauna.